2018
DOI: 10.3389/fmech.2018.00020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Alternative Octane Specification Methods for Improved Gasoline Knock Resistance in Spark-Ignition Engines

Abstract: Different octane specification methods were evaluated under rising ethanol blending volumes by adopting a refinery economics model to represent a region in the U.S. It was demonstrated that the traditional octane specification methods, such as the Anti-knock Index (AKI) used in the U.S., or the Research Octane Number (RON) and Motor Octane Number (MON) used in the EU, can lead to counterintuitive drop in octane sensitivity with increased availability of ethanol. This is undesirable for modern gasoline engines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The framework utilizes recent methods from the field of generative graph-ML and GNNs to design molecules with high-knock resistance for modern SI engines. Specifically, we set out to maximize the sum of RON and OS, hence the OI, as high-efficiency SI engines require both a high RON and a high OS (Kalghatgi, 2005;Bell, 2010;Mittal and Heywood, 2008;Amer et al, 2012;Kalghatgi, 2014;Szybist and Splitter, 2017;Abdul-Manan et al, 2018). We show a high-level overview of our framework in Figure 1 and provide a detailed framework overview including our choices for algorithms and models in the three different modules in Figure 4.…”
Section: Graph-based Property Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework utilizes recent methods from the field of generative graph-ML and GNNs to design molecules with high-knock resistance for modern SI engines. Specifically, we set out to maximize the sum of RON and OS, hence the OI, as high-efficiency SI engines require both a high RON and a high OS (Kalghatgi, 2005;Bell, 2010;Mittal and Heywood, 2008;Amer et al, 2012;Kalghatgi, 2014;Szybist and Splitter, 2017;Abdul-Manan et al, 2018). We show a high-level overview of our framework in Figure 1 and provide a detailed framework overview including our choices for algorithms and models in the three different modules in Figure 4.…”
Section: Graph-based Property Predictionmentioning
confidence: 99%
“…The weighted sum of RON and OS is referred to as the octane index (OI) (Kalghatgi, 2001). For modern SI engines, fuels with both high RON and high OS, hence high OI, are desired as they enable engine operation at conditions associated with particularly high efficiency (Kalghatgi, 2005;Bell, 2010;Mittal and Heywood, 2008;Amer et al, 2012;Kalghatgi, 2014;Szybist and Splitter, 2017;Abdul-Manan et al, 2018). To boost the OI of a fuel, chemical species with high RON and high OS such as ethanol and MTBE can be added (Demirbas et al, 2015;Badia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, many recent studies [2,3] have determined that modern spark ignition (SI) engines are better served by an antiknock rating called octane index (OI), given by…”
Section: Introductionmentioning
confidence: 99%
“…RON has been identified as more important for modern engine performance. However, it is increasingly reported that the knock-limited performance of modern engines may be further enhanced by having lower MON for a given RON. The term octane sensitivity (OS = RON – MON) is commonly used to describe this attribute, with higher OS being considered advantageous. The explanation for this benefit relates to the in-cylinder temperature and pressure trajectories under knock-limited operation in modern SI engines. , The chemical kinetics associated with the combustion of fuels with high OS yield longer ignition delays as the temperature decreases for a given pressure. Consequently, high OS fuels exhibit greater knock resistance in modern SI engines and are, therefore, better suited for enabling efficiency gains relative to low OS fuels.…”
Section: Introductionmentioning
confidence: 99%